2014
DOI: 10.1186/s12879-014-0661-6
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency is associated with community-acquired clostridium difficile infection: a case–control study

Abstract: BackgroundClostridium difficile infection (CDI) is increasingly recognized as an important community acquired pathogen causing disease (CA-CDI). Vitamin D [25(OH)D] has immune modulatory effects and plays an important role in intestinal immunity. The role of vitamin D in CA-CDI has not been examined previously.MethodsThis was a single referral center case–control study. Cases comprised of all patients with CA-CDI who had a serum 25(OH)D measured within 12 months prior to infection. Controls were drawn from pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 42 publications
0
17
0
1
Order By: Relevance
“…In contrast to one year mortality, we identified 25(OH)D at admission to hospital as an independent predictor of postoperative medical complications which is in line with the majority of surgical outcome studies [ 26 ]. This result is also confirmed by several studies exhibiting an association between vitamin D deficiency and increased susceptibility to infections [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 53%
“…In contrast to one year mortality, we identified 25(OH)D at admission to hospital as an independent predictor of postoperative medical complications which is in line with the majority of surgical outcome studies [ 26 ]. This result is also confirmed by several studies exhibiting an association between vitamin D deficiency and increased susceptibility to infections [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 53%
“…22 Recent studies have demonstrated the relationship between vitamin D deficiency and infectious diseases. 23,24 Vitamin D regulates the innate immune system in macrophages against Myco- …”
Section: Discussionmentioning
confidence: 99%
“…4 Among the included studies, 3 reported 25(OH)D concentrations by C difficile diagnosis outcome (infected vs noninfected). 4,14,15 Three studies 5,6,16 assessed the association between 25(OH)D status (<20 ng/mL vs ≥20 ng/ mL) and CDI severity (mild vs severe). Finally, 4 studies 5,12,13,16 examined the association between 25(OH)D status (<20 ng/mL vs ≥20 ng/mL) and CDI recurrence (see Table 1).…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%